INTERNAL FORMATION MECHANISM OF CONSTRUCTION COMPANY INNOVATION MODELING DEVELOPMENT - N. Moiseenko; O. Kuzmina (Вестник университета)
Innovative development path of the construction company makes it necessary to adapt the internal environment to the constantly changing market conditions in order to successfully implementation of economic and administrative organization problems. This article considers an analysis of the main internal environment factors of a construction company, which have the most significant effect on the ability of innovation modeling activity. Based on the results of the analysis, the author proves a need for the new in-house climate to improve innovation activity of the construction organization.